2021
DOI: 10.3390/md19010031
|View full text |Cite
|
Sign up to set email alerts
|

Specific Antiproliferative Properties of Proteinaceous Toxin Secretions from the Marine Annelid Eulalia sp. onto Ovarian Cancer Cells

Abstract: As Yondelis joins the ranks of approved anti-cancer drugs, the benefit from exploring the oceans’ biodiversity becomes clear. From marine toxins, relevant bioproducts can be obtained due to their potential to interfere with specific pathways. We explored the cytotoxicity of toxin-bearing secretions of the polychaete Eulalia onto a battery of normal and cancer human cell lines and discovered that the cocktail of proteins is more toxic towards an ovarian cancer cell line (A2780). The secretions’ main proteins we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 86 publications
1
11
0
Order By: Relevance
“…Initially, the results showed that the crude venom and its fraction B had the ability to reduce the viability of CLL B-lymphocytes. These results are in agreement with previous studies that have shown that the use of venoms extracted from marine animals is associated with a decrease in the viability of various cancer cell lines (Catanesi et al, 2021;Rodrigo et al, 2021). Studies have shown that there is an inverse relationship between cell viability and apoptotic signaling (Li et al, 2020;Wang et al, 2020).…”
Section: Fraction B Increased Ros Generation In Cll Blymphocytessupporting
confidence: 93%
“…Initially, the results showed that the crude venom and its fraction B had the ability to reduce the viability of CLL B-lymphocytes. These results are in agreement with previous studies that have shown that the use of venoms extracted from marine animals is associated with a decrease in the viability of various cancer cell lines (Catanesi et al, 2021;Rodrigo et al, 2021). Studies have shown that there is an inverse relationship between cell viability and apoptotic signaling (Li et al, 2020;Wang et al, 2020).…”
Section: Fraction B Increased Ros Generation In Cll Blymphocytessupporting
confidence: 93%
“…After 0 h, 30 min, 1 h, 3 h, or 6 h of incubation, the cells were fixed with 4% (w/v) formaldehyde (Sigma-Aldrich, Merck, Kenilworth, NJ) for 15 min and washed three times with PBS. The cell membrane was then disrupted by a 5 min incubation with 0.1% (v/v) Triton (Sigma-Aldrich, Merck) and washed three times with PBS, and the cells were incubated for 30 min with 1% (w/v) bovine serum albumin (BSA; NZYtech, Lisbon, Portugal) and 20 min with AlexaFluor 488 phalloidin (Invitrogen, ThermoFisher Scientific), as previously described . After washing three times with PBS, the cells were visualized with an Eclipse Ti–U inverted microscope with a green filter cube (an excitation filter range at 465–495 nm and an emission filter range at 515–555 nm), and images were acquired with the respective microscope software.…”
Section: Methodsmentioning
confidence: 99%
“…The cell membrane was then disrupted by a 5 min incubation with 0.1% (v/v) Triton (Sigma-Aldrich, Merck) and washed three times with PBS, and the cells were incubated for 30 min with 1% (w/v) bovine serum albumin (BSA; NZYtech, Lisbon, Portugal) and 20 min with AlexaFluor 488 phalloidin (Invitrogen, ThermoFisher Scientific), as previously described. 71 After washing three times with PBS, the cells were visualized with an Eclipse Ti−U inverted microscope with a green filter cube (an excitation filter range at 465−495 nm and an emission filter range at 515−555 nm), and images were acquired with the respective microscope software. Three different images with around 20 cells were acquired per sample with a 40× objective, or five different images with around five cells were acquired with a 100× objective.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The combination of transcriptomics and proteomics research over the past few years has also resulted in significant advances in the identification of potential drugs from marine toxins, while improvements in liquid chromatography-tandem mass spectrometry made this task more achievable (Xie et al, 2017). The importance of research in this area can be exemplified by the identification of bioproducts capable of interfering with specific pathways, allowing the development of anti-cancer treatments (Rodrigo et al, 2021). Rodrigo et al (2021) discovered that a cocktail of proteins from Eulalia sp.…”
Section: Prospecting Bioactive Peptides From Marine Organismsmentioning
confidence: 99%
“…The importance of research in this area can be exemplified by the identification of bioproducts capable of interfering with specific pathways, allowing the development of anti-cancer treatments (Rodrigo et al, 2021). Rodrigo et al (2021) discovered that a cocktail of proteins from Eulalia sp. is more toxic toward an ovarian cell line (A2780), supporting the potential of mixed proteins in venoms against aggressively proliferating cells.…”
Section: Prospecting Bioactive Peptides From Marine Organismsmentioning
confidence: 99%